Peningkatan Pengetahuan Ibu Hamil Tentang Skrinning HIV/AIDS Melalui Audiovisual di Wilayah Kerja Puskesmas Andalas - Gina Muthia; Eka Putri Primasari; Putri Nelly Syofiah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
In addition to preventing problems for pregnant women and their babies, the aim of quality antenatal care is to detect the emergence of these problems early and avoid negative impacts on health. This includes HIV infection. HIV prevalence in pregnant women is projected to increase from 0.38% (2012) to 0.49% (2016). Data for pregnant women infected with HIV at Puskesmas Andalas in 2017 was in the range of 1,600. It is known that data on the implementation of VCT at Puskesmas Andalas, in 2017 (January - Jun 2017) there were only 250 VCT patients, consisting of 224 pregnant women and 26 non-pregnant women, meaning that in the working area of ​​the Andalas Puskesmas only 14% of pregnant women participated to do an HIV test (VCT). Therefore, it is necessary to have community service activities to increase knowledge about HIV / AIDS screening in pregnant women. The results of the activity were counseling to 6 pregnant women from 10 target people in the Pustu Sarang Gagak Andalas Village, Padang. The output is in the form of publication of articles in public service journals that are E-ISSN and nationally accredited, social media and increasing knowledge about HIV / AIDS screening of pregnant women.